Malaysian sugar industry: is there a competitive advantage? - Jabir, Nur Alina; Ismail, Mohd Mansor (School of Social Sciences, Universiti Sains Malaysia, 2012)
The paper outlined a look into the trend of competitive advantage of sugar industry, as well as the growth in trade especially from the context of Balance of Trade (BOT) perspective. The competitive advantage of Malaysia’s sugar sector is examined from the aspect of Relative Export Advantage (RXA), Relative Import Advantage (RMA), and Relative Trade Advantage (RTA), and the results were then compared to that of selected ASEAN countries for competitive positioning. The trade data used for the analysis is the annual exports and imports data retrieved from the Global Trade Information System. The results indicate that Malaysia is not competitive in raw sugar but possesses competitive potential in processed sugar. However, the competitiveness level is declining.